Blood vessel invasion as a strong independent prognostic indicator in non-small cell lung cancer: a systematic review and meta-analysis. - Jun Wang; Jianpeng Chen; Xi Chen; Baocheng Wang; Kainan Li; Jingwang Bi (PLoS ONE)
Background and objective Blood vessel invasion plays a very important role in the progression and metastasis of cancer. However, blood vessel invasion as a prognostic factor for survival in non-small cell lung cancer (NSCLC) remains controversial. The aim of this study is to explore the relationship between blood vessel invasion and outcome in patients with NSCLC using meta-analysis. Methods A meta-analysis of published studies was conducted to investigate the effects of blood vessel invasion on both relapse-free survival (RFS) and overall survival (OS) for patients with NSCLC. Hazard ratios (HRs) with 95% confidence intervals (95% CIs) were used to assess the strength of this association. Results A total of 16,535 patients from 52 eligible studies were included in the systematic review and meta-analysis. In total, blood vessel invasion was detected in 29.8% (median; range from 6.2% to 77.0%) of patients with NSCLC. The univariate and multivariate estimates for RFS were 3.28 (95% CI: 2.14-5.05; P<0.0001) and 3.98 (95% CI: 2.24-7.06; P<0.0001), respectively. For the analyses of blood vessel invasion and OS, the pooled HR estimate was 2.22 (95% CI: 1.93-2.56; P<0.0001) by univariate analysis and 1.90 (95% CI: 1.65-2.19; P<0.0001) by multivariate analysis. Furthermore, in stage I NSCLC patients, the meta-risk for recurrence (HR = 6.93, 95% CI: 4.23-11.37, P<0.0001) and death (HR = 2.15, 95% CI: 1.68-2.75; P<0.0001) remained highly significant by multivariate analysis. Conclusions This study shows that blood vessel invasion appears to be an independent negative prognosticator in surgically managed NSCLC. However, adequately designed large prospective studies and investigations are warranted to confirm the present findings.